Between race changes in segment speed and stroking patterns in Paralympic individual medley swimmers - Daly, D.; Gardiki, S.; Birzinyte, K.; Schega, L.; Vanlandewijck, Y. (First international symposium sciences and practices in swimming, 2006)
Because of the complexity of the race it might be difficult for a coach to decide which athletes are best suited for the individual medley event especially in Paralympic swimmers with diverse loco-motor impairments. The purpose here was to determine how race segment speed and stroking variables changed between heat and final swims in the Paralympic Individual Medley event and how this was related to Overall changes in race result. Segment speeds were measured on video tapes for 46 Sydney Paralympic 200-m Individual Medley finalists. Changes in backstroke speed were most related to overall changes in end race result. Changes in butterfly speed were least related. Changes in Stroke rate were more related to these between race changes than changes in Stroke length especially in the asymmetric freestyle and backstroke Segments.